1993
DOI: 10.1152/jn.1993.69.2.384
|View full text |Cite
|
Sign up to set email alerts
|

Relation between electrophysiological class and neuropeptide content of guinea pig sympathetic prevertebral neurons

Abstract: 1. Sympathetic neurons in superior mesenteric ganglion and inferior mesenteric ganglion (IMG) isolated from guinea pigs were classified as tonic, phasic, or long after hyperpolarizing (LAH) on the basis of their discharge characteristics and the different types of potassium currents recorded from them with the soma under single-microelectrode voltage clamp. 2. Passive electrical properties showed a progressive increase in input resistance across the prevertebral ganglia in the rostrocaudal direction when compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
39
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 0 publications
4
39
0
Order By: Relevance
“…Previous studies have demonstrated correlations between the neurochemistry, projections, major inputs, and presumably the function of neurons in the guinea pig celiac ganglion that supplies sympathetic nerves to the small bowel (Macrae et al, 1986;Keast et al, 1993;L uckensmeyer andKeast, 1995, 1996). These data also support the idea that immunohistochemically defined subsets of IMG neurons represent chemically coded groups with distinct functions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have demonstrated correlations between the neurochemistry, projections, major inputs, and presumably the function of neurons in the guinea pig celiac ganglion that supplies sympathetic nerves to the small bowel (Macrae et al, 1986;Keast et al, 1993;L uckensmeyer andKeast, 1995, 1996). These data also support the idea that immunohistochemically defined subsets of IMG neurons represent chemically coded groups with distinct functions.…”
Section: Discussionmentioning
confidence: 98%
“…Some IMG neurons also contain neuropeptide Y immunoreactivity (N PY neurons; ϳ20% of IMG neurons), and other subsets include those containing somatostatin (SOM neurons; ϳ75%), both N PY and SOM (N PY/SOM neurons; 4 -7%), or neither N PY nor SOM (Ϫ/Ϫ neurons; 1-5%) (Elf vin et al, 1993;Sann et al, 1995;Parr and Sharkey, 1996). Most or all NPY neurons project to the vasculature (Furness et al, 1983), whereas SOM and Ϫ/Ϫ neurons project to the myenteric and submucosal plexuses of the enteric nervous system (ENS) in the wall of the colon (Keast et al, 1993;Parr and Sharkey, 1996).…”
Section: Abstract: Neuropeptide Y; Somatostatin; Prevertebral Ganglimentioning
confidence: 99%
“…The idea that several types of cardiac ganglion cell may exist in the guinea-pig is supported by immunohistochemical studies; several different types of cardiac ganglion cell can be distinguished on the basis of their neuropeptide content (Steele, Gibbins, Morris & Mayer, 1994). In other peripheral ganglia, populations of ganglion cells with different combinations of neuropeptides have been found to have different electrical properties (Furness & Costa, 1987;Keast, McLachlan & Meckler, 1993 …”
mentioning
confidence: 99%
“…Two firing patterns, phasic and tonic, have been described in various intact sympathetic ganglia isolated in vitro from several species (see Adams and Harper, 1995). Detailed analyses have identified a third class of cell in ganglia from guinea pigs (Cassell and McLachlan, 1987;Christian and Weinreich, 1988;McLachlan and Meckler, 1989;Keast et al, 1993), rabbits (Cassell and McLachlan, 1987) and rats (L. Melnichenko and E. McLachlan, unpublished observations). These have been called long-afterhyperpolarising (LAH) neurones; they discharge phasically but have an afterhyperpolarisation lasting seconds.…”
mentioning
confidence: 99%
“…They form the predominant population in different anatomical locations: phasic (Ph ) neurones in the paravertebral chain, tonic (TI neurones in the inferior mesenteric ganglion, and LAH neurones in the coeliac ganglion. Further, the passive electrical properties of the neurones differ not only between the classes but also, within one class, between locations (Keast et al, 1993). Finally, neurones of each class receive different patterns of synaptic input: P h and LAH neurones receive at least one suprathreshold preganglionic input in addition to several subthreshold ones (Hirst and McLachlan, 1984;McLachlan and Meckler, 1989).…”
mentioning
confidence: 99%